Água em condição supercrítica: uma tecnologia versátil para o tratamento de efluentes industriais e produção de hidrogênio - Ribeiro, Thiago Soares Silva (2021)
Industrial processes bring with them an important concern: the correct management of waste generated, whether solid, liquid or gaseous. Among the various types of industrial wastewater, those generated in pharmaceutical industries that produce hormonal drugs or in biodiesel producing plants stand out for their polluting potential and high organic load, respectively. Therefore, it is essential to perform the appropriate treatment of these industrial wastewater, which does not occur in many of the conventional processes used in wastewater treatment stations (WTS). In this scenario that the objective of this work was to treat samples of hormonal (synthetic (EHS) and industrial (EHI)) wastewater, in addition to samples of wastewater from a biodiesel producing plant (EPB) using the process with supercritical water (SCWP), in a continuous flow reactor in the absence of catalysts, aiming at the degradation of contaminants and obtaining hydrogen gas, syngas and other fuel gases. The use of samples with such a different chemical composition is justified by the intention to evaluate the versatility of the wastewater treatment via SCWP for both environmental and energy purposes. The liquid phase was characterized by the determination of physical-chemical parameters such as total organic carbon (TOC), Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Oils and Greases (OG), pH, nitrogen compounds, metals, among others, in addition to high performance liquid chromatography (HPLC), for EHS samples, mass spectrometry (EM), and phytotoxicity tests with cucumber seeds (Cucumis sativus). The gas phase was characterized by gas chromatography (GC). Regarding the reduction of TOC, it was possible to reduce between 80% and 90% of TOC in the EHS samples for most of the feed flow rate conditions evaluated at 700 °C and for the EHI samples the maximum value of 89 was obtained, 6% reduction in TOC at the highest temperature evaluated. In EPB samples, the maximum TOC reduction value reached was 98.8%. The other physical-chemical parameters analyzed point to the same trend: the higher the temperature and the spatial time, the greater the efficiency of the process in relation to the reduction of physical-chemical parameters. The phytotoxicity tests against cucumber seeds, indicate a significant reduction in the toxic effect of the chemical compounds present in the initial samples, in treatments from 600 °C. The results of mass spectrometry point to the predominance of esters and fatty acids in both samples analyzed. The characterization of the gases showed that the production of hydrogen gas stands out among the other gases, and the amount produced in the treatment of EPB samples (885.9 NmL(H2)/mL (powered EPB)) indicates several possibilities of using this gas in industrial processes such as Ammonia Production, Production of new compounds via Fischer-Tropsch process, Fuel cells, Burning as fuel, Hydrotreated vegetable oil (HVO) manufacturing processes, Power-to-X technologies (PtX). In view of the results, it is possible to infer that the treatment of organic contaminants via SCWP is quite promising for both energy and environmental purposes.